Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.pedn.2016.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Cigarette Refill Liquids: Child-Resistant Packaging, Nicotine Content, and Sales to Minors

Abstract: Purpose To determine the accuracy of the labeled quantity of the nicotine content of the e-liquids sold in unlicensed vape stores, whether the packaging of e-liquids sold within the vape stores was child-resistant, whether minors were present within vape stores, and whether sales to minors occurred. This study was conducted across North Dakota prior to implementation of a new e-cigarette state law and provided a baseline assessment before enactment of the new legal requirements. Design and Methods We tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 13 publications
0
33
1
1
Order By: Relevance
“…5,6,108180 Ten additional studies were published on methods to analyze ENDS liquids and vapor. 181190 One study measured hazardous waste potential of ENDS disposal.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…5,6,108180 Ten additional studies were published on methods to analyze ENDS liquids and vapor. 181190 One study measured hazardous waste potential of ENDS disposal.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…(These reports may underestimate nicotine exposure because 8%–12% of students responded “don't know” to questions about e-cigarette contents, 1, 2, 4 and e-cigarettes labeled “nicotine-free” often contain nicotine. 5, 6 ) Nicotine exposure during adolescence can affect memory, attention, and emotional regulation. 7 E-cigarette aerosol has been linked to cell damage, 8 lung inflammation, asthma, 9 and respiratory infections.…”
mentioning
confidence: 99%
“…Although some companies already include health warnings on their packaging voluntarily, there is no enforcement of the accuracy of these warnings, and previous studies have shown that the ingredients of e-liquids often differ from those listed on the packaging. 21,22 For example, liquids labeled as 0% nicotine have been found to contain nicotine, 23 and some liquids labeled as containing caffeine or other "energy" ingredients actually did not contain those ingredients. 24 This this study was purely observational and did not educate the participants about the possibility of incorrect or misleading warning labels.…”
Section: Discussionmentioning
confidence: 99%